Drug-eluting beads transcatheter arterial chemoembolization combined with systemic therapy versus systemic therapy alone as first-line treatment for unresectable colorectal liver metastases - Wang, Fuquan; Chen, Lei; Bin, Chai; Cao, Yanyan; Wang, Jihua; Zhou, Guofeng; Zheng, Chuansheng (Frontiers in Oncology, 2024)
The purpose of this retrospective study was to compare the therapeutic efficacy and safety of drug-eluting bead transarterial chemoembolization (DEB-TACE) combined with systemic therapy to systemic therapy alone as first-line treatment for unresectable patients with colorectal liver metastases (CRLM).Methods: From December 2017 to December 2022, patients with unresectable CRLM who received systemic therapy with or without DEB-TACE as first-line treatment were included in the study. The primary endpoint was progression-free survival (PFS). Secondary endpoints were tumor response, conversion rate and adverse events.Results: Ninety-eight patients were enrolled in this study, including 46 patients who received systemic therapy combined with DEB-TACE (DEB-TACE group) and 52 patients who received systemic therapy alone (control group). The median PFS was elevated in the DEB-TACE group compared with the control group (12.1 months vs 8.4 months, p = 0.008). The disease control rate was increased in the DEB-TACE group compared with the control group (87.0% vs 67.3%, p = 0.022). Overall response rates (39.1% vs 25.0%; p = 0.133) and conversion rate to liver resection (33.8% vs 25.0%; p = 0.290) were no different between the two groups. The multivariate analysis showed that treatment options, size of liver metastasis, number of liver metastasis, synchronous metastases, and extrahepatic metastases were independent prognostic factor of PFS. Further subgroup analyses illustrated that PFS was beneficial with the DEB-TACE group in patients with age ≥ 60, male, left colon, synchronous metastases, bilobar, number of liver metastasis > 5, extrahepatic metastases, non-extrahepatic metastases, CEA level < 5 (ng/ml), and KRAS wild-type. No grade 4 or 5 toxicities related to DEB-TACE procedures were observed.According to Reviewer 2's comment 1 suggestion, we have rewritten this part of the content.